HISTORIOGRAFI PESANTREN: PERSPEKTIF METODOLOGIS ANTARA ADA DAN TIADA - Sayono, Joko (Jurnal Sejarah dan Budaya, 2010)
Abstract: There are many writings of pesantren (Islamic Boarding School), but only few of them have approprite standart of history writing (historiography). In spite of its independent mozaik, the story of pesantren has been recorded since its born It is necessary to investigate it deeper in term of methodological perspective, because pesantren as a enclave gives picture about journey of a society culture. The well done historiography of pesantren will give contribution to understand pesantren community rightly.